Altsiedelkerne und frühkolonialer Ausbau in der Bewässerungskulturlandschaft Zentralchiles - Weischet, Wolfgang.; Schallhorn, E. (ERDKUNDE, 1974)
For the irrigated cultural landscape of Central Chile the problem has to be solved of how to find out the first onsets, the early cores of development of the irrigated fields. Analyzing the pattern of parcels of different agricultural landscapes by means of aerial photographs in this area, distinct small cells could be isolated. They differ from all other areas by the geometric shape of their parcels, their comparatively small size, and their characteristic mutual arrangement. As far as the physiogeographicconditions of their location is concerned, all of them are located at places of optimum waters upply and land-use conditions in the area in the age before irrigation systems had been installed. Furthermore, both physiogeographic and human geographic features of the irrigated fields in the nearby areas lead to the conclusion that the above-described nuclei must be considered as isolated cores of early settlements and land use based on irrigation, and at the same time the innovation centers of irrigated field systems.